2017
DOI: 10.12681/mms.1980
|View full text |Cite
|
Sign up to set email alerts
|

Polychaete fauna from the intertidal zone of the Kneiss Islands (central Mediterranean Sea)

Abstract: The spatial and temporal distribution, abundance and assemblage structure of polychaete communities in the Kneiss Islands (central Mediterranean Sea) was studied at 42 stations selected among seagrass Zostera (Zosterella) noltei Hornemann meadows and unvegetated habitats sampled from April 2014 to January 2015. The Kneiss Islands represent a site of international interest in terms of their ornithological diversity (Important Bird Area, Ramsar Site and SPAMI). A total of 18,026 individuals and 92 species of pol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 36 publications
1
10
0
Order By: Relevance
“…Some inventories for polychaetes cover the entire Mediterranean Sea (Arvanitidis et al, 2002;Castelli et al, 2008;Coll et al, 2010), while others are limited to certain areas: Moroccan waters (both the Atlantic and Mediterranean coasts) (Gillet, 2017), the Mediterranean coast of France (Laubier & Paris, 1962;Dauvin et al, 2006), Italian waters (Castelli et al, 1995(Castelli et al, , 2008, the Adriatic Sea (Musco, 2012;Mikac, 2015), the Tunisian coasts (Ayari et al, 2009;Zaâbi et al, 2012, Mosbahi et al, 2017, the Aegean Sea (Ergen, 1976;Simboura & Nicolaidou, 1994, 2001Arvanitidis, 2000;Ergen et al, 2002Ergen et al, , 2006Faulwetter et al, 2017), the Levantine Sea (Laubier, 1966;Ben-Eliahu, 1995;Çinar, 2005, 2007Mutlu et al, 2010;Faulwetter et al, 2017;Dorgham et al, 2013Dorgham et al, , 2014, the Turkish coastline (Çinar et al, 2014) and the Black Sea (Arvaniditis et al, 2002;Şahin & Çinar, 2012). However, no complete inventory is available for the 1200km of Algerian coastline.…”
Section: Introductionmentioning
confidence: 99%
“…Some inventories for polychaetes cover the entire Mediterranean Sea (Arvanitidis et al, 2002;Castelli et al, 2008;Coll et al, 2010), while others are limited to certain areas: Moroccan waters (both the Atlantic and Mediterranean coasts) (Gillet, 2017), the Mediterranean coast of France (Laubier & Paris, 1962;Dauvin et al, 2006), Italian waters (Castelli et al, 1995(Castelli et al, , 2008, the Adriatic Sea (Musco, 2012;Mikac, 2015), the Tunisian coasts (Ayari et al, 2009;Zaâbi et al, 2012, Mosbahi et al, 2017, the Aegean Sea (Ergen, 1976;Simboura & Nicolaidou, 1994, 2001Arvanitidis, 2000;Ergen et al, 2002Ergen et al, , 2006Faulwetter et al, 2017), the Levantine Sea (Laubier, 1966;Ben-Eliahu, 1995;Çinar, 2005, 2007Mutlu et al, 2010;Faulwetter et al, 2017;Dorgham et al, 2013Dorgham et al, , 2014, the Turkish coastline (Çinar et al, 2014) and the Black Sea (Arvaniditis et al, 2002;Şahin & Çinar, 2012). However, no complete inventory is available for the 1200km of Algerian coastline.…”
Section: Introductionmentioning
confidence: 99%
“…The granulometric analyses revealed that there were four groups of sediment types in the intertidal zone of the Kneiss Islands (previously described in Mosbahi et al, 2017). Zostera noltei eelgrass beds colonized all the sampled stations.…”
Section: Environmental Parametersmentioning
confidence: 67%
“…Sampling consisted of collecting the topmost 20 cm of the sediment, being carried out at 32 stations in April 2014, in areas corresponding to fully extended Z. noltei seagrass beds (Figure 1). The sediment analyses (proportions of mud, fine sand, medium sand and coarse sand) and organic matter contents measured in the sediment are the same as those reported in a previous paper on polychaete structure and seasonal patterns (Mosbahi, Dauvin, & Neifar, 2017).…”
Section: Sampling and Laboratory Proceduresmentioning
confidence: 78%
“…The identi ed taxa were classi ed into six trophic groups according to the categories used by many authors (e.g A i et Jumars et al 2014;Mosbahi al. 2017Mosbahi al.…”
Section: Benthic Indicesmentioning
confidence: 99%
“…However, there are few quantitative studies designed to examine soft-bottom communities and the impacts of NIS in soft sediment habitats (Travizi et al 2019). In Tunisia, the majority of benthic macrofauna studies have focused on macrobenthic communities of shallow coastal areas (i.e Khedhri et al 2014;Fersi et al 2018;Boudaya et al 2019;Mosbahi et al 2017Mosbahi et al , 2019Mosbahi et al and 2020.…”
Section: Introductionmentioning
confidence: 99%